The Relationship Between Parenting Patterns And Parental Motivation In Conducting Toilet Training For Preschool Age Children In Kademangan Village - Sandra Waki’ah Prihatini; Feriana Ira Handian; Sismala Harningtyas (PROFESSIONAL HEALTH JOURNAL, 2024)
Introduction: Preschool age is a stage where children learn to be able to urinate and defecate independently, which if there is a delay will have an impact on health problems. The purpose of this study was to determine the relationship between parenting style and parental motivation in toilet training for parents.This research design uses a correlational quantitative design with a crosswhich,sectional approach. Objectives: Parents who have preschool-age children are expected to provide proper care at this stage so as not to become late. Methods: A sample of 40 parents who had preschool-age children delay,determined by the total sampling method. The instruments used in this study were parenting questionnaires and parental motivation for toilet training. The Spearman-Rho. test is used in analyzing data. Results: The results of self-testing obtained a value of p = (0.001) < (0.05) and a value of r = 0.524, which means that there is a positive relationship related to parenting style and parental motivation in doing toilet training in pre-school children in Kademangan Village with moderate correlation strength. Which means that the more fixed the parenting style, the higher the motivation parents have to do toilet training. Conclusions: For Further Researchers The next researcher found out other factors in the parenting style applied to children. Meanwhile, to motivate parents in carrying out toilet training in preschool children, future researchers must also know other factors besides parenting patterns. Apart from that, future researchers can conduct research in villages that have problems that are almost the same as this case